1996
DOI: 10.1074/jbc.271.10.5633
|View full text |Cite
|
Sign up to set email alerts
|

Defective Fatty Acid-mediated β-Cell Compensation in Zucker Diabetic Fatty Rats

Abstract: Although obesity is associated with insulin resistance, most obese humans and rodents remain normoglycemic because of compensatory hyperinsulinemia. This has been attributed to ␤-cell hyperplasia and increased low K m glucose metabolism of islets. Since free fatty acids (FFA) can induce these same ␤-cell changes in normal islets of Wistar rats and since plasma FFA are increased in obesity, FFA could be the signal from adipocytes that elicits ␤-cell compensation sufficient to prevent diabetes. To determine if F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 33 publications
7
91
0
1
Order By: Relevance
“…Previously it has been shown that inhibition of fatty acid oxidation by an inhibitor of CPT1 reduces basal hypersecretion in ZDF rats, such that the maintenance of fatty acid oxidation may also be important in compensation processes [38]. Islets of the ZF rat displayed none of the well-described features of lipotoxicity [7,[39][40][41][42][43]. The TG content was mildly decreased rather than dramatically increased [7,40].…”
Section: Discussionmentioning
confidence: 93%
“…Previously it has been shown that inhibition of fatty acid oxidation by an inhibitor of CPT1 reduces basal hypersecretion in ZDF rats, such that the maintenance of fatty acid oxidation may also be important in compensation processes [38]. Islets of the ZF rat displayed none of the well-described features of lipotoxicity [7,[39][40][41][42][43]. The TG content was mildly decreased rather than dramatically increased [7,40].…”
Section: Discussionmentioning
confidence: 93%
“…An additional increase in islet fat reverses the foregoing compensatory changes and causes b-cell disfunction, a reduction in the b-cell proliferation, and diabetes (Milburn et al, 1995;Hirose et al, 1996;Shimabukuro et al, 1998b). The b-cell descompensation in this type of diabetes may involve excessive nitric oxide (NO) generation through inducible NO synthase .…”
Section: Effect Of Ffa On B-cell Apoptosismentioning
confidence: 99%
“…However, there is no effective therapy for inflammation or for DNP. LncRNAs, typically defined as transcripts longer than 200 nucleotides, are recently regarded as a potential therapeutic target for inflammatory relevant diseases, including diabetes and DNP [26][27][28][29][30][31][32][33][34][35][36][37][38]. However, the functional question of massive lncRNAs in DNP has not been characterized [26,27,30].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were grouped into control (25 mM Dglucose), HG 50 mM (50 mM D-glucose), and HG 75 mM (75 mM D-glucose). FFAs were a mixture of oleate and palmitate, 2:1 (w/w) [34]. For HF experiment, the cells were grouped into control (1 % BSA), HF 0.25 mM, HF 0.5 mM, and HF 1.0 mM [6].…”
Section: Cell Culturementioning
confidence: 99%